Rancang Bangun Sistem Informasi Sekolah Berbasis Website (Studi Kasus : SDIT Azzhahiriyah) - Naufal Muyassar; Wahyu Hadikristanto; Muhamad Fatchan (DPPM Universitas Pelita Bangsa, 2022)
The progress of science and technology at this time shows that speed, convenience, and security are the main considerations and benchmarks in facing global challenges. Information systems must be able to be effective and efficient in providing a series of information flow processes to improve the quality and quantity and satisfaction of clients or work partners.